In vitro screening of effectiveness and antiproliferative effects of potential DDIT4 inhibitors for breast cancer cell lines - E. M. Zhidkova; D. D. Grigoreva; E. S. Lylova; V. P. Maksimova; G. R. Sagitova; G. I. Khayrieva; E. S. Trapeznikova; K. I. Kirsanov; M. G. Yakubovskaya; E. A. Lesovaya (Сибирский онкологический журнал)
Objective: screening of previously selected DDIT4 inhibitors by their ability to suppress basal and glucocorticoid-induced expression of this gene in breast cancer (BC) cells, as well as evaluation of antiproliferative and cytotoxic effects of the studied drug combinations the antiproliferative and proapoptotic effects of studied drug combinations. Material and Methods. Breast cancer cells of the luminal, HER2- positive and triple negative subtypes were used. The effects of drugs (rapamycin, wortmannin, LY-294002, apigenin, resveratrol, curcumin, CGP-60474, and emetine) on the basal and glucocorticoid-induced levels of expression of the DDIT4 gene and its protein product were evaluated by qPCR and Western blotting assays. Results. Emetine, rapamycin, wortmannin, LY-294002 and CGP-60474 demonstrated DDIT4-inhibition activity. Glucocorticoid dexamethasone showed cytotoxic effects and antiproliferative activity in combination with emetine, CGP-60474 (C protein kinase inhibitor), resveratrol and curcumin. Conclusion. Novel inhibitors of DDIT4 in breast cancer model cells in vitro were found. Emetine and CGP-60474 are the most promising drugs for further research.